Answer: The average rate of change of the function in that interval is r = -1
Explanation:
When we have a function f(x), the average rate of change in an interval:
a ≤ x ≤ b
Is calculated as:
![rate = (f(b) - f(a))/(b - a)](https://img.qammunity.org/2022/formulas/mathematics/high-school/nlhbdwno7o299wdsh0favykjzhuhkt1dun.png)
In this case, the function is:
y = f(x) = (1/2)*x^2 - 1
And the interval is:
-2 ≤ x ≤ 0
Then the rate of change will be:
![rate = (f(0) - f(-2))/(0 -(-2)) = (((1/2)*(0)^2 - 1) -((1/2)(-2)^2 - 1))/(2) = (-2)/(2) = -1](https://img.qammunity.org/2022/formulas/mathematics/high-school/2adwf1d5if9l4dqo0gmamfvepmfqcfva9p.png)
The average rate of change of that function in that interval is r = -1